Positive Allosteric Modulation of CB1 Cannabinoid Receptor Signaling Enhances Morphine Antinociception and Attenuates Morphine Tolerance Without Enhancing Morphine- Induced Dependence or Reward - Slivicki, Richard A.; Iyer, Vishakh; Mali, Sonali S.; Garai, Sumanta; Thakur, Ganesh A.; Crystal, Jonathon D.; Hohmann, Andrea G. (Frontiers in Molecular Neuroscience, 2020)
Opioid analgesics represent a critical treatment for chronic pain in the analgesic ladder of the World Health Organization. However, their use can result in a number of unwanted side-effects including incomplete efficacy, constipation, physical dependence, and overdose liability. Cannabinoids enhance the pain-relieving effects of opioids in preclinical studies and dampen unwanted side-effects resulting from excessive opioid intake. We recently reported that a CB1 positive allosteric modulator (PAM) exhibits antinociceptive efficacy in models of pathological pain and lacks the adverse side effects of direct CB1 receptor activation. In the present study, we evaluated whether a CB1 PAM would enhance morphine’s therapeutic efficacy in an animal model of chemotherapy-induced neuropathic pain and characterized its impact on unwanted side-effects associated with chronic opioid administration. In paclitaxel-treated mice, both the CB1 PAM GAT211 and the opioid analgesic morphine reduced paclitaxel-induced behavioral hypersensitivities to mechanical and cold stimulation in a dose-dependent manner. Isobolographic analysis revealed that combinations of GAT211 and morphine resulted in anti-allodynic synergism. In paclitaxel-treated mice, a sub-threshold dose of GAT211 prevented the development of tolerance to the anti-allodynic effects of morphine over 20 days of once daily dosing. However, GAT211 did not reliably alter somatic withdrawal signs (i.e. jumps, paw tremors) in morphine-dependent neuropathic mice challenged with naloxone. In otherwise naïve mice, GAT211 also prolonged antinociceptive efficacy of morphine in the tail-flick test and reduced the overall right-ward shift in the ED50 for morphine to produce antinociception in the tail-flick, consistent with attenuation of morphine tolerance. Pretreatment with GAT211 did not alter somatic signs of µ opioid receptor dependence in mice rendered dependent upon morphine via subcutaneous implantation of a morphine pellet. Moreover, GAT211 did not reliably alter µ-opioid receptor-mediated reward as measured by conditioned place preference to morphine. Our results suggest that a CB1 PAM may be beneficial in enhancing and prolonging the therapeutic properties of opioids while potentially sparing unwanted side-effects (e.g. tolerance) that occur with repeated opioid treatment.